2013
DOI: 10.1371/journal.pone.0053566
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quality of Clinical Practice Guidelines for Otorhinolaryngology in China

Abstract: ObjectiveTo evaluate the quality of clinical practice guidelines (CPGs) for otorhinolaryngology in China.Materials and MethodsA systematic search of relevant literature databases (CBM, WANFANG, VIP, CNKI, China Guideline Clearinghouse) published between 1978 and March 2012 was undertaken to identify and select CPGs related to otorhinolaryngology. Four independent reviewers assessed the eligible guidelines using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument. Their degree of agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…The finding of low scores for Croatian guidelines in most of AGREE domains (“Rigour of Development”, “Stakeholder Involvement”, “Applicability” and “Editorial Independence) is similar to the finding for other national guidelines, as recently published for the general population of guidelines and specific otorhinolaryngology guidelines in China [3], [4]. Like in China, Croatian guidelines have mostly been developed as expert opinions, which generally followed the methodology and presentation of a literary review, rather than methodologically rigorous analysis of evidence.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The finding of low scores for Croatian guidelines in most of AGREE domains (“Rigour of Development”, “Stakeholder Involvement”, “Applicability” and “Editorial Independence) is similar to the finding for other national guidelines, as recently published for the general population of guidelines and specific otorhinolaryngology guidelines in China [3], [4]. Like in China, Croatian guidelines have mostly been developed as expert opinions, which generally followed the methodology and presentation of a literary review, rather than methodologically rigorous analysis of evidence.…”
Section: Discussionsupporting
confidence: 79%
“…They are produced not only by international organizations but also by professional associations in many countries, aiming to supply the local professionals with recommendations based on currently available evidence for best standard of care for the patients [2][4].…”
Section: Introductionmentioning
confidence: 99%
“…The Appraisal of Guidelines for Research and Evaluation (AGREE) instrument was initially developed in 2003, and updated to AGREE II in 2010. Consisting of 6 domains covering 23 key items [12] , it is an appraisal tool and validated instrument that has been endorsed by leading producers, raters and compilers of international CPGs to provide a framework for assessing their quality [13] . Previous studies have demonstrated that the quality of CPGs in different clinical areas was modest or variable [13] – [16] .…”
Section: Instructionmentioning
confidence: 99%
“…Furthermore, as aggregate scoring across domains is not recommended by the AGREE Enterprise, the AGREE II Global Rating Scale (AGREE IIGRS) was used to rate overall quality on a 7point scale (from 1 = lowest quality to 7 = highest quality) and categorized as: "excellent quality"= score 7/7, "high quality" = 5-6/7, "moderate quality" = 4/7 and "poor quality" = 0-3/7. The AGREEII instrument is a validated appraisal tool for thorough quality assessment of guidelines and is widely used (18)(19)(20)(21)(22)(23)(24).…”
Section: Evaluation Of Included Clinical Practice Guidelinesmentioning
confidence: 99%